2017
DOI: 10.5152/tud.2016.86155
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of uropathogen and their antibiotic resistance pattern among diabetic patients

Abstract: Objective: Diabetes mellitus (DM) and antibiotic resistance is an emerging public health problem in Ethiopia. Urinary tract infections (UTIs) are common and occasionally life-threatening condition among diabetic patients. Despite, all these problems, antibiotics are prescribed empirically which may adversely affect antibiotic resistance so far. Therefore the aim of this study was to identify the etiologic agents of UTI and their antibiotic resistance pattern among diabetic patients attending diabetic clinic of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
62
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(116 citation statements)
references
References 16 publications
(22 reference statements)
26
62
15
Order By: Relevance
“…This was relatively comparable with a study conducted in Nekemte, Ethiopia (80.6%) [ 13 ], and Gondar, Ethiopia (80.2%) [ 11 ]. The higher resistance in S. aureus to tetracycline (85.7%) and nitrofurantoin (85.7%) was in line with a study conducted in Gondar, Ethiopia [ 11 ], and Hawassa, Ethiopia [ 14 ]. The similarity might be attributed to poor adherence to antibiotics, the use of antibiotics as a prophylactic treatment, easy availability, and indiscriminate use of antimicrobials by health professionals and patients.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This was relatively comparable with a study conducted in Nekemte, Ethiopia (80.6%) [ 13 ], and Gondar, Ethiopia (80.2%) [ 11 ]. The higher resistance in S. aureus to tetracycline (85.7%) and nitrofurantoin (85.7%) was in line with a study conducted in Gondar, Ethiopia [ 11 ], and Hawassa, Ethiopia [ 14 ]. The similarity might be attributed to poor adherence to antibiotics, the use of antibiotics as a prophylactic treatment, easy availability, and indiscriminate use of antimicrobials by health professionals and patients.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the odds of developing UTI were significantly higher for diabetic patients who had a history of UTI than for those who had no history of UTI. This was consistent with previous studies conducted in Nekemte, Ethiopia [ 13 ], but it was contradicted with a study conducted in Hawassa, Ethiopia [ 14 ], which showed a diabetic patient with no previous history of UTI had higher odds of UTI. The possible explanation for the difference might be due to relapse of the infection as a result of ineffective treatment and the presence of high concentration of sugar in diabetic urine, which serves as a media for a proliferation of pathogenic bacteria, or recall bias [ 6 , 7 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…29 However, it was relatively higher than the study performed in Addis Ababa (13.6%), 15 Debre Tabor (19%), 16 Hawassa (23.1%), 25 Harar (20%), 14 and Sudan (17.1%). 13 On the other hand, the prevalence of asymptomatic UTI (9.4%) was comparable with studies conducted in Addis Ababa (10.4%), 15 Hawassa (11.2%), 25 and Harar (12.4%), 14 but lower than similar study reports from Gondar (14.7%), 26 Debre Tabor (80.9%), 16 and Sudan (20.9%). 13 Such variations might also be due to differences in risk factors with geographical areas, sample size, study population, and deployment of diverse methodologies.…”
Section: Discussionmentioning
confidence: 80%
“…[5][6][7] High prevalence of infection, irrational uses of antibiotics, over-the counter availability of antibiotics and poor infection prevention practices leads to emergence of multi drug resistance. 8 In the context of this, present study was undertaken with the aims to study the various uropathogens and their sensitivity pattern, so that this knowledge can be utilized for betterment of the community as well as for controlling the drug resistance.…”
Section: Introductionmentioning
confidence: 99%